Linguistik Perspektif Ferdinand De Saussure dan Ibn Jinni - Dian Risky Amalia (Institut Agama Islam Negeri Metro, 2019)
Many studies of scientists who study the thoughts of Ferdinand De Saussure and Ibn Jinni on linguistics in particular, because both of them are monumental figures with real contributions in the civilization of linguistics or linguistics. Uncovering both theoretically is very influential in the development of linguistics. The father of modern linguistics is Ferdinand de Saussure, and the famous Arabic linguist, Ibn Jinni, the thoughts of the two figures become a valuable heritage in the world of scientific scholarship. The research method used is the library research. Researchers collect primary and secondary data in processing research material. Ferdinand de Saussure with his achievements as a linguist has laid the foundations of linguistic thinking such as langue-parole, significant-signified, arbitrary-motivated, and syntagmatic-paradigmatic. And so is Ibn Jinni who has formulated various terminologies about differences Kalam and Qaul, al-Luhgah ‘language’, arbiters as the basis for selecting letters and also word planners, and qiyas made it a method of creating new languages. Both figures equally consider the interrelationship of language and time, and the influence of social forces that influence language so that Saussure began the study of language by synchronic methods, not just diachronic. Where Ibn Jinni also uses social ta'lil, which is all returned to the speakers of the language it selfs. This research contributes in establishing linguistics that cannot be separated from the time and social that exists in that place.